Europejskie koncepcje samorządu terytorialnego - POKŁADECKI, Jacek (Przegląd Politologiczny, 2018)
Territorial self-government is one of the fundamental institutions of a modern democratic state of law. There are numerous European traditions of self-government that have produced different concepts and, consequently, different theories of territorial self-government. The most important ones include the naturalist, state, and political theories. Each of them shows a different picture of the origin, essence and the scope of legal personality a territorial self-government has, of local communities, the position of the administrative unit of the commune and higher units. Depending on the concept one chooses, political and organizational solutions are differentiated, as are the tasks of territorial self-government units, the competences of its organs and the authority of state organs to exercise control and supervision. On the basis of the solutions adopted in every country, and at a given level of development of the state, the degree of decentralization of power, the degree of autonomy, self-reliance and independence of territorial self-government is determined.